Natural hazards management in Asia - Pal, Indrajit; Ghosh, Tuhin (SAGE Publications, Incorporated, 2018)
Natural disasters are more common now than they have been ever before. Globally, climates are changing and natural hazards are becoming routine. This book is a study of natural hazards and how they turn into disasters-with a focus on Asian countries. It takes a holistic view of the subject and discusses different concepts of disaster management to understand both theory as well as practice. The book also explains best practices and the most effective tools for alleviating the consequences of such disasters.